2013
DOI: 10.5267/j.msl.2013.01.034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social capital on knowledge creation in Petrochemical Industry

Abstract: Knowledge creation and innovation are primary competitive advantage in the modern economy. Social capital, on the other hand, is one the most important components of organizations, which could help share knowledge within organization and create competitive advantage. The purpose of this paper is to investigate the impact of social capital on knowledge creation in petrochemical industry. The survey designs a questionnaire and distributes it among some experts who worked for petrochemical industry. The study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…(2012) showed: All dimensions of IC have a significant impact on dimensions of knowledge creation. Saadi and Pahlavani (2012) confirmed that all three IC items positively influence knowledge creation, significantly. Darvisha et.…”
Section: Literature Reviewsupporting
confidence: 55%
“…(2012) showed: All dimensions of IC have a significant impact on dimensions of knowledge creation. Saadi and Pahlavani (2012) confirmed that all three IC items positively influence knowledge creation, significantly. Darvisha et.…”
Section: Literature Reviewsupporting
confidence: 55%
“…Saadi and Pahlavan (2013), for instance, investigated the effect of social capital on knowledge creation in Petrochemical industry. They studied the effect of social capital in terms of three components of cognitive, relational and structural capitals on knowledge creation and confirmed that all three items positively impact knowledge creation, significantly.…”
Section: Introductionmentioning
confidence: 99%